2016
DOI: 10.1016/j.riit.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Use of Artificial Neural Networks for Prediction of the Convective Heat Transfer Coefficient in Evaporative Mini-Tubes

Abstract: In this work, artificial neural networks (ANNs) are used to characterize the convective heat transfer rate that occurs during the evaporation of a refrigerant flowing inside tubes of very small diameter. An experimental setup based on an inverse Rankine refrigeration cycle is used to obtain the heat transfer data in an R-134a refrigerant mini-tube evaporator set operated under constant heat flux conditions. A considerable amount of data was acquired to map the thermal performance of the evaporative process und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Artificial neural network (ANN) is a computing system that solves problems by imitating mechanisms of the human brain. It has been applied to various engineering applications, including convective heat transfer [48][49][50][51][52] and boiling [53][54][55][56][57][58] to estimate desired performance parameters with adequate experimental data. Scalabrin et al [53,54] modeled heat transfer of flow boiling in horizontal tubes for different fluids using ANN and found that the flow boiling heat transfer model does not fundamentally depend on the flow pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural network (ANN) is a computing system that solves problems by imitating mechanisms of the human brain. It has been applied to various engineering applications, including convective heat transfer [48][49][50][51][52] and boiling [53][54][55][56][57][58] to estimate desired performance parameters with adequate experimental data. Scalabrin et al [53,54] modeled heat transfer of flow boiling in horizontal tubes for different fluids using ANN and found that the flow boiling heat transfer model does not fundamentally depend on the flow pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Several predictive models have been developed in the literature for estimating the convective heat transfer coefficient [31]. Artificial neural networks are frequently used in the creation of these models [32][33][34][35]. Another classification and estimated model method using regression is decision trees [36].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural networks are usually used to construct these models [7][8][9][10]. Predictive models of h c values were created by using SVM regression in different topics [11,12].…”
Section: Introductionmentioning
confidence: 99%